PENERAPAN PEMBELAJARAN KOOPERATIF PENDEKATAN THINK PAIR SQUARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII2 SMP NEGERI 4 SIAK HULU - Mentari, Dyah; ', Syofni; Murni, Atma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was based on the students achievement in learning mathematics especially grade VIII2 of SMP Negeri 4 Siak Hulu under the Mastery Minimum Criteria with percentage of 23,07% on the test about Tribe Factorization Algebra. This research is a class action research. This research aims to improve the learning process and improve learning result in mathematics in grade VIII2 of SMP Negeri 4 Siak Hulu by implementation of cooperative learning with Think Pair Square (TPS) approach. The subject of this research were the students in the class VIII2 of SMP Negeri 4 Siak Hulu that consist of 18 boys and 21 girls at the first semester of academic year 2016/2017. The instruments of data collection in this research were observation sheets and student’s mathematic tests. The observation sheets were analyzed in desciptive narative, while the student’s mathematic tests were analyzed in statistic desciptive. The descriptive narative showed an improvement of learning process prior to the action on the first and second cycles. The results of this research showed an increasing number of students learning mathematic from the basic score with percentage 23,07% to 38,46% on the first test and 61,53% on second test. The frequency distribution analysis as well showed an improvement student achievement are increasing the number of student who received higher criteria on the first test and second test compared the number of student who received higher criteria on the basic score. On the low criteria, the number of student at interval 21–40 descreased from basic score to the first test and second test. Furthermore, on the higher criteria, the number of student at interval 81-100 increased from basic score to first test with 3 students into 15 students, then have increased on the second test with 23 students. Based on the result of this research could be concluded that the implementation of cooperative learning with Think Pair Square (TPS) Approach can improve the learning process and improve the student’s achievement of learning mathematic in grade VIII2 of SMP Negeri 4 Siak Hulu in the first semester academic years 2016/2017.Key Word : Mathematical Achievement, Cooperative Learning, Think Pair Square Approach, Clasroom Action Research